Rancangan Tata Letak Penyimpanan Bahan Baku Menggunakan Metode Class-Based Storage Berdasarkan Turnover Ratio di Gudang PT X Bandung - Sumerta Dana, I Kadek Hendra; Rizal, Muhammad; Aulia Hakim, Raden Marsha (STKIP Singkawang, 2024)
This study examines the implementation of the class-based storage method in designing the raw material storage layout at the PT X Bandung warehouse. Currently, raw materials are stored randomly, resulting in inefficiencies such as increased travel distances, difficulty in locating items, and higher physical workload for warehouse operators. To address these issues, the class-based storage method is applied by categorizing materials based on their movement frequency using FSN (Fast, Slow, and Non-Moving) Analysis, enabling more optimal placement.Data was collected through direct measurement of item movement distances in both the current and proposed layouts, supported by warehouse layout simulations. The results indicate that implementing this method reduced the total movement distance from 1,194,342 cm to 948,294 cm, representing a 20.6% reduction, thereby significantly improving operational efficiency.Moreover, the combination of dedicated and shared storage allows for more flexible space utilization, especially for returned raw materials. It is recommended that PT X integrate this method with periodic demand reviews and staff training to ensure sustained warehouse performance and more streamlined logistics processes